Contemporary extended pelvic lymph node dissection for prostate cancer in the UK – an analysis of national practice - Calleja, E; Reilly, G; Fowler, S; McGrath, J; Sooriakumaran, P; Aning, J (Elsevier, 2017)
Extended pelvic lymph node dissection (ePLND) is accepted as the optimal method of lymph node staging in prostate cancer. In the UK radical prostatectomy has been performed in specialist centres since 2002. Since 2014 as part of a NHS transparency drive, contributing data to the BAUS national registry has been accepted as good medical practice for surgeons performing radical prostatectomy and compliance is high. To date there has been no national review of lymph node dissection practice or analysis of the new prostate cancer grading systems ability to detect lymph node invasion. We report a detailed analysis of UK ePLND for localised prostate cancer practice and lymph node invasion rates.